Sequential implementation of the EQUIPPED geriatric medication safety program as a learning health system. (16th July 2020) - Vandenberg, Ann E; Kegler, Michelle; Hastings, S Nicole; Hwang, Ula; Wu, Daniel; Stevens, Melissa B; Clevenger, Carolyn; Eucker, Stephanie; Genes, Nick; Huang, Wennie; Ikpe-Ekpo, Edidiong; Nassisi, Denise; et al.
Abstract: Objectives: To present the three-site EQUIPPED academic health system research collaborative, which engaged in sequential implementation of the EQUIPPED medication safety program, as a learning health system; to understand how the organizations worked together to build resources for program scale-up. Design: Following the Replicating Effective Programs framework, we analyzed content from implementation teams' focus groups, local and cross-site meeting minutes and sites' organizational profiles to develop an implementation package. Setting: Three academic emergency departments that each implemented EQUIPPED over three successive years. Participants: Implementation team members at each site participating in focus groups ( n  = 18), local meetings during implementation years, and cross-site meetings during all years of the projects. Intervention(s): EQUIPPED provides Emergency Department providers with clinical decision support (education, order sets, and feedback) to reduce prescribing of potentially inappropriate medications to adults aged 65 years and older who received a prescription at time of discharge. Main Outcome Measure(s): Implementation process components assembled through successive implementation. Results: Each site had clinical and environmental characteristics to be addressed in implementing the EQUIPPED program. We identified 10 process elements and describe lessons for each. Lessons guided the compilation of the EQUIPPED intervention package or toolkit, including the EQUIPPED logic model. Conclusions: Our academic health system research collaborative addressing medication safety through sequential implementation is a learning health system that can serve as a model for other quality improvement projects with multiple sites. The network produced an implementation package that can be vetted, piloted, evaluated, and finalized for large-scale dissemination in community-based settings.